2000
DOI: 10.1210/jcem.85.10.6887
|View full text |Cite
|
Sign up to set email alerts
|

Early Identification of Children Predisposed to Low Peak Bone Mass and Osteoporosis Later in Life1

Abstract: The amount of bone that is gained during adolescence is the main contributor to peak bone mass, which, in turn, is a major determinant of osteoporosis and fracture risk in the elderly. We examined whether computed tomography measurements for the density and the volume of bone in the axial and the appendicular skeletons could be tracked through puberty in 40 healthy white children (20 girls and 20 boys). Longitudinal measurements of the cross-sectional area and cancellous bone density of the vertebral bodies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…During growth, the skeleton adapts its size, shape and material properties to be of sufficient strength to support the evolving physical activity (Currey and Butler, 1975;Jee and Frost, 1992;Loro et al, 2000;Palacio-Mancheno et al, 2014;Parfitt et al, 2000). Histomorphometric studies highlighted that this adaptation was made possible through changes in modeling and remodeling activity and its balance at both the tissue and the Bone Multicellular Unit (BMU) level (Parfitt et al, 2000;Rauch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During growth, the skeleton adapts its size, shape and material properties to be of sufficient strength to support the evolving physical activity (Currey and Butler, 1975;Jee and Frost, 1992;Loro et al, 2000;Palacio-Mancheno et al, 2014;Parfitt et al, 2000). Histomorphometric studies highlighted that this adaptation was made possible through changes in modeling and remodeling activity and its balance at both the tissue and the Bone Multicellular Unit (BMU) level (Parfitt et al, 2000;Rauch et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that porosity achieved during growth may influence intracortical remodeling and structural decay later in life (Bala et al, 2014b;Bjornerem et al, 2013;Bui et al, 2013;Loro et al, 2000;Seeman, 2008). Haversian and Volkmann's canal density, size and connectivity in young adult defines indeed the extent of surfaces available for unbalanced remodeling to be initiated upon at the onset of age-related perturbation at the BMU level (Bui et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that AP has either positive or negative effects on BMD (4,6,17,18). One study suggested that AP may affect the physiological processes of bone metabolism and therefore adversely affect peak bone mass (16).…”
Section: Discussionmentioning
confidence: 99%
“…Data using pQCT in healthy children are summarised in Appendix 3. 106,[121][122][123][124][125][126] In a cohort study, Loro and colleagues examined whether pQCT could identify children predisposed to low peak BMD and osteoporosis in later life. 126 Forty healthy white children were followed for 3 years.…”
Section: Qct Data From Healthy Childrenmentioning
confidence: 99%